Comparative Effectiveness of Dialyzers: A Longitudinal, Propensity Score-Matched Study of Incident Hemodialysis Patients. Issue 5 (September 2016) - Sibbel, Scott; Hunt, Abigail; Laplante, Suzanne; Beck, Werner; Gellens, Mary; Brunelli, Steven M.
Abstract : Differences in dialyzer design may have consequences for patient outcomes. We evaluated the comparative effectiveness of commonly used dialyzers with respect to measures of dialysis treatment, anemia management, inflammation, and dialyzer clotting. Patients receiving hemodialysis between January 1, 2009, and December 31, 2013, and using polyarylethersulfone–polyvinylpyrrolidone (PAS-PVP; Polyflux Revaclear) or polysulfone (PS; Optiflux 160 or Optiflux 180) dialyzers were followed for 1 year or until end of study or censoring for dialyzer switch, modality change, or loss to follow-up. For each comparison, eligible patients were propensity score-matched 1:1 on a range of baseline characteristics. Outcomes were assessed using generalized linear mixed models. Dialysis adequacy was similar in both dialyzer groups. Erythropoiesis-stimulating agent (ESA) doses were lower for patients using PAS-PVP versus patients using PS-160 (difference range: 75–589 units/treatment; statistically significant in months 1–5 and 7) and for patients using PAS-PVP versus patients using PS-180 (difference range: 27–591 unit/treatment; statistically significant in months 1–9). Intravenous iron doses trended lower for patients using PAS-PVP versus patients using PS, but hemoglobin concentrations were equivalent. In conclusion, use of PAS-PVP versus PS dialyzers was associated with equivalent dialysis adequacy, lower ESA doses, modestly lower Intravenous iron doses, and equivalent hemoglobin concentrations. Abstract : Supplemental Digital Content is available in the text.